Analisis perbedaan literasi keuangan sebelum dan sesudah mendapatkan edukasi keuangan - Susi Sulastry Lomi; Lusianus Heronimus Sinyo Kelen (Universitas Negeri Padang, 2021)
The micro, small and medium-sized enterprises sector in Indonesia has been increased but the level of financial literacy is still low, as a consequence financial education is needed. With the financial education provided, businessmen can manage finances, credit, savings, and investment, and risk management. This study aims to analyze the differences in financial literacy before and after receiving financial education in the district of Waingapu. The sample of this research is 150 respondents. The result found that there were significant differences in financial literacy before and after receiving financial education.